PELATIHAN PEMBUATAN PUPUK ORGANIK CAIR DENGAN MEMANFAATKAN LIMBAH ORGANIK RUMAH TANGGA DI SUNGKAI UTARA - Yeyen Ilmiasari; Yuni Elmita Sari; Nyang Vania Ayuningtyas Harini (Sentra Kekayaan Intelektual dan Publikasi Ilmiah, 2026)
The problem of household organic waste and dependence on chemical fertilizers remains a challenge in Sungkai Utara District. This community service activity aims to improve community knowledge and skills in managing household organic waste into environmentally friendly and useful liquid organic fertilizer (POC). The activity implementation method uses a participatory approach through the stages of initial surveys, counseling, direct practice of making POC, mentoring, and monitoring and evaluation. The results of the activity showed an increase in participant knowledge from 36% to 84%. Participants were able to produce approximately 120 liters of liquid organic fertilizer and apply it to yard plants. The impact of the activity includes reduced household organic waste, increased community independence in providing fertilizer, and growing awareness of environmental management and sustainable agriculture. This activity has the potential to be replicated as a community service model based on the utilization of household organic waste.